2020
DOI: 10.1007/s00228-020-02860-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and risk factors of tigecycline-associated hypofibrinogenaemia in critically ill patients

Abstract: Purpose To analyze the clinical features and risk factors of tigecycline-associated hypofibrinogenaemia and study whether cefoperazone/sulbactam combined with tigecycline aggravates coagulopathy or hypofibrinogenaemia. Methods A retrospective case-control study of patients with severe infection who were treated with tigecycline was conducted. Patients were assigned to the hypofibrinogenaemia group (< 2.0 g/L) and normal fibrinogen (normal) group (≥ 2.0 g/L) to assess the clinical features of patients with tige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
42
2
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 37 publications
11
42
2
7
Order By: Relevance
“…According to our research, hypofibrinogenemia was common in clinical practice, which occurred in 60.8% of the patients. This is in agreement with prior reports: in Hu’s research, 14 there were 56% developed hypofibrinogenemia, and in Zhang’s research, 15 there were 50.5% developed hypofibrinogenemia, respectively. Fibrinogen decreased by an average of 49.2%, PT, aPTT and TT increased by an average of 16.8%, 19.5% and 26.7%, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…According to our research, hypofibrinogenemia was common in clinical practice, which occurred in 60.8% of the patients. This is in agreement with prior reports: in Hu’s research, 14 there were 56% developed hypofibrinogenemia, and in Zhang’s research, 15 there were 50.5% developed hypofibrinogenemia, respectively. Fibrinogen decreased by an average of 49.2%, PT, aPTT and TT increased by an average of 16.8%, 19.5% and 26.7%, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Hu’s study also showed there is no correlation between hypofibrinogenemia and age. 14 But in their study, the age of the hypofibrinogenemia group was 63.72±15.68 years old, and that of the normal group was 55.82±18.59 years old, which were much smaller than the age of the patients in our study. Our study can better reflect the effect of tigecycline on coagulation in elderly patients.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations